2020
DOI: 10.3390/en13112980
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Crude Oil Prices under the Impact of COVID-19 by Using LSTARGARCHLSTM

Abstract: Under the influence of the COVID-19 pandemic and the concurrent oil conflict between Russia and Saudi Arabia, oil prices have exhibited unusual and sudden changes. For this reason, the volatilities of the West Texas Intermediate (WTI), Brent and Dubai crude daily oil price data between 29 May 2006 and 31 March 2020 are analysed. Firstly, the presence of chaotic and nonlinear behaviour in the oil prices during the pandemic and the concurrent conflict is investigated by using the Shanon Entropy and Lyapunov expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 55 publications
3
41
0
Order By: Relevance
“…For comparison of the models, Mean Absolute Percentage Error (MAPE) metric is used to measure the size of the error in percentage terms regarding the actual values. The metrics like Mean Absolute Error (MAE) [36] , the Mean Square Error (MSE) [12] , Root Mean Square Error (RMSE) [ 10 , 26 , 37 ], suffer from non-normalized measurements and accordingly provide higher values for countries with more population.. Therefore, we selected MAPE, which offers a normalized version that is more comparable between different sizes of the population.…”
Section: Methodsmentioning
confidence: 99%
“…For comparison of the models, Mean Absolute Percentage Error (MAPE) metric is used to measure the size of the error in percentage terms regarding the actual values. The metrics like Mean Absolute Error (MAE) [36] , the Mean Square Error (MSE) [12] , Root Mean Square Error (RMSE) [ 10 , 26 , 37 ], suffer from non-normalized measurements and accordingly provide higher values for countries with more population.. Therefore, we selected MAPE, which offers a normalized version that is more comparable between different sizes of the population.…”
Section: Methodsmentioning
confidence: 99%
“…Oil market: The pandemic has caused a chaotic behavior in the oil prices. To analyze the price of crude oil under the impact of the pandemic, an AI based method is proposed in [548] . Due to the pandemic, fuel demand plummeted and in some cases the price of oil future went negative.…”
Section: Applications Of Ai In Epidemiologymentioning
confidence: 99%
“…Lahmiri [3], Bildirici, and Sonustun [4]; Komijani et al [5]; and He [6] are the other studies that determine the presence of chaos in the oil prices. Bildirici et al [7] suggested a new hybrid modelling technique based on the LSTARGARCH and LSTM models to analyze the volatility of oil prices.…”
Section: Introductionmentioning
confidence: 99%